Analysis model of binary code security flaws based on structure characteristics - Tuan XU; Lei-lei QU; Wen-chang SHI (网络与信息安全学报)
Aiming at the shortcomings of the existing methods to detect the security flaws that have complex structures,a new analysis model and its application method was proposed.First,analysis models based on key information of code structures extracted from path subsets of characteristic element sets that are generated by source code element sets of code security flaws were constructed.Then the analysis model according to the statistical probability of each kind of IR statement was calculated,and the IR code group which matched the feature model was found.Finally,through the translating relation between binary codes and IR codes,various code security flaws of binary program were found out.The analysis models can be applied to both common single-process binary programs and binary parallel programs.Experimental results show that compared with the existing methods,the application of the analysis model can be more comprehensive and in-depth in detecting various types of complex binary code security flaws with higher accuracy.